Flipped Classroom: Its Implementation and Impact in Science Learning (A Case Study During the Covid-19 Pandemic) - Eka Supriasih; Apit Fathurohman; Ida Sriyanti (Universitas Muhammadiyah Makassar, 2023)
Flipped classroom is a sort of blended learning in which students learn both synchronously and asynchronously. Synchronous learning has taken place in the classroom in real time. Learners gather feedback while communicating with teachers and classmates at the same time. This review expects to figure out how is the execution and effect of Flipped Classroom in Science Learning (Contextual analysis During the Covid-19 Pandemic) of Class VIII at SMPN 3 Rantau Bayur. This study used a case study as an approach in exploring qualitative data. This examination is a distinct subjective exploration as a contextual analysis with information assortment methods as polls and meetings. The results of this review demonstrate that the execution and effect of flipped classroom in science learning during the Covid-19 pandemic is positive, particularly for class VIII students in science subjects at SMPN 3 Rantau Bayur with a typical rate gain of 76.7% or the category of ‘very good’. Through the flipped classroom, students have the opportunity to concentrate on the topic at home as they are free to set their learning time. Students become familiar with the topic in an enjoyable situation. Students can repeat the learning videos and they are able to access them from anywhere. Besides, parents can participate in learning activities outside the classroom and make time to help their children learn. However, one of the drawbacks is the lack of devices to watch videos given by the teacher as not all students have computers, laptops, or smartphones. Also, the teachers still find difficulties in preparing good quality videos as learning media for students.